2017
DOI: 10.1016/j.nicl.2016.12.013
|View full text |Cite
|
Sign up to set email alerts
|

Primary visual cortical remapping in patients with inherited peripheral retinal degeneration

Abstract: Human studies addressing the long-term effects of peripheral retinal degeneration on visual cortical function and structure are scarce. Here we investigated this question in patients with Retinitis Pigmentosa (RP), a genetic condition leading to peripheral visual degeneration. We acquired functional and anatomical magnetic resonance data from thirteen patients with different levels of visual loss and twenty-two healthy participants to study primary (V1) visual cortical retinotopic remapping and cortical thickn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
64
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(67 citation statements)
references
References 105 publications
3
64
0
Order By: Relevance
“…It has been shown that retinotopic eccentricity may be shifted in patients with RP such that central retinal inputs are represented in more peripheral locations in V1 15. However, it has also been shown that task-dependent stimuli can result in BOLD responses being detectable in relation to a previously unresponsive ‘lesion projection zone’,26 but which may not relate to any cortical reorganisation.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that retinotopic eccentricity may be shifted in patients with RP such that central retinal inputs are represented in more peripheral locations in V1 15. However, it has also been shown that task-dependent stimuli can result in BOLD responses being detectable in relation to a previously unresponsive ‘lesion projection zone’,26 but which may not relate to any cortical reorganisation.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, some human fMRI studies have shown responses in the LPZ (Baker et al 2005, Baker et al 2008, Dilks et al 2009) or shifts in measured cortical retinotopic organization (Ferreira et al 2017) in late blind individuals suffering from visual field loss due to retinal dystrophies, while other studies have failed to find evidence for reorganization (Masuda et al 2008, Masuda et al 2010, Baseler et al 2011). …”
Section: Adult Plasticitymentioning
confidence: 95%
“…All the neurophysiological (Kaas et al 1990, Gilbert and Wiesel 1992, Darian-Smith and Gilbert 1995, Abe et al 2015) and fMRI (Baseler et al 2011, Ferreira et al 2017) studies that did find shifts in retinal organization in V1 used methods susceptible to this modeling confound. Indeed Baseler et al (2011) found dramatic shifts in cortical retinotopic organization in late blind macular degeneration patients.…”
Section: Adult Plasticitymentioning
confidence: 99%
“…Furthermore, pRF modeling allowed us to quantitatively assess potential alterations of pRF characteristics in the visual cortex in the face of retinal lesions (Barton and Brewer, 2015;Baseler et al, 2011), developmental disorders Carvalho et al, 2019;Hoffmann et al, 2012;Hoffmann and Dumoulin, 2015) and trauma (Haak et al, 2014;Halbertsma et al, 2019;Papanikolaou et al, 2014). While alterations could be interpreted as evidence for potential cortical remapping and as an explanation for changes in fMRI responses following visual field defects (Baker et al, 2008;Dilks et al, 2009;Ferreira et al, 2017;Zhou et al, 2017), there is growing evidence for more conservative views on the nature and extent of adult visual cortex plasticity (Masuda et al, 2010(Masuda et al, , 2008Wandell and Smirnakis, 2009). E.g., larger pRFs in the lesion projection zones (LPZ) in the primary visual cortex in patients with macular degeneration were also evident in controls with simulated lesions (Barton and Brewer, 2015;Baseler et al, 2011;Haak et al, 2012), thus questioning the concept of large-scale long-term reorganization in the visual cortex.…”
Section: Introductionmentioning
confidence: 99%
“…While this bias has been well investigated in the lesion projection zone for deprived foveal stimulation (Haak et al, 2012;Morland, 2015), studies on the pRF dynamics in the normal projection zone associated of the fovea during deprived peripheral stimulation are currently emerging. In fact, recent investigations of patients with peripheral visual field defects, due to retinitis pigmentosa (RP) (Ferreira et al, 2017) or glaucoma (Zhou et al, 2017), report a displacement of pRFs in the normal projection zone, i.e., foveal pRFs to parafoveal or eccentric position. These shifts were taken as evidence for cortical remapping, in comparison to healthy controls with intact VF representations.…”
Section: Introductionmentioning
confidence: 99%